2019
DOI: 10.20343/teachlearninqu.7.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Creative Innovation Takes a (Team Teaching) Family

Abstract: Team teaching can be a valuable means of enabling cross-disciplinary collaboration, interdisciplinary study, and pedagogical innovation, but the logistical and intellectual challenges can seem too daunting to overcome. Here, we share the story of how four faculty members from professional writing, communications, and computing sciences developed a team teaching "family" as we imagined, created, launched, and ran an innovative experiential learning program at our university. The Design Thinking Studio in Social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…We all explain solutions to problems a bit differently, which can help “unlock” programming principles for a wider array of learners. Team teaching also has other benefits, such as greater professional and social support for instructors [ 14 ].…”
Section: Rule 2: Teach As a Teammentioning
confidence: 99%
“…We all explain solutions to problems a bit differently, which can help “unlock” programming principles for a wider array of learners. Team teaching also has other benefits, such as greater professional and social support for instructors [ 14 ].…”
Section: Rule 2: Teach As a Teammentioning
confidence: 99%
“…We all explain solutions to problems a bit differently, which can help "unlock" programming principles for a wider array of learners. Team teaching also has other benefits, such as greater professional and social support for instructors [13].…”
Section: Rule 2: Teach As a Teammentioning
confidence: 99%
“…Although prior studies have shown DT can positively impact teaching and learning within higher education (Haigh and Withell 2020;Lake, Flannery, and Kearns 2021;Lake, Lehman, and Chamberlain 2019;Lake, Motley, and Moner 2019;McLaughlin et al 2022;Pope-Ruark, Motley, and Moner 2019), little research has explored the potential role of DT when it comes to liberatory teaching and learning praxis and philosophies (Noel 2022;Udoewa 2022). In addition, few studies analyze data from the perspectives of faculty and student within multiple disciplines and institutions of higher education.…”
Section: Introductionmentioning
confidence: 99%